Certain biochemical changes in uterine fluid during follicular and luteal phases of estrous cycle and certain reproductive disorders in buffaloes - RAJU, K G S; RAO, K S; REDDY, K C S (The Indian Journal of Animal Reproduction, 2007)
The uterine fluid obtained after flushing from genitalia of36 slaughtered buffaloes was collectedseperately. Biochemical assay on the flushing revealed that total protein levels were significantly higher in luteal phase of the cycle, and,from genitalia showing mucometra as against those tracts having smooth ovaries or endometritis. No significant change in albumin levels during two phases ofestrous cycle, as well as, in smooth ovaries and endometritis was seen, except that of tracts suggestiveofmucometra. In mucometra the level was higher. Globulin levels were significantly higher in lutealphase and mucometra condition. Albumin to globulin ratio was higher in conditions of smooth ovariesand endometritis. Alkaline phosphatase activity was significantly higher in follicular phase of estrouscycle. Cholesterol levels recorded were highest in follicular phased followed by mucometra and Iutealphase of the cycle.
Keywords: Biochemical Profiles; Uterine Flushing; Reproductive conditions; Buffaloes